Stochastic Processes : Selected Papers on Hiroshi Tanaka. - Maejima, Makoto (World Scientific Publishing Company, 2002)
Hiroshi Tanaka is noted for his discovery of the "Tanaka formula", which is a generalization of the Itô formula in stochastic analysis. This important book is a selection of his brilliant works on stochastic processes and related topics. It contains Tanaka's papers on (i) Brownian motion and stochastic differential equations (additive functionals of Brownian paths and stochastic differential equations with reflecting boundaries), (ii) the probabilistic treatment of nonlinear equations (Boltzmann equation, propagation of chaos and McKean-Vlasov limit), and (iii) stochastic processes in random e.